Cementless Total Knee Arthroplasty: A Review - Cherian, Jeffrey J.; Banerjee, Samik; Kapadia, Bhaveen H.; Jauregui, Julio J.; Harwin, Steven F.; Mont, Michael A. (The Journal of Knee Surgery, 2014)
There is ongoing debate over the use of cementless fixation in total knee arthroplasty (TKA). Previous generation prostheses resulted in less than optimal outcomes which was somewhat attributed to design issues. As the demand for TKA is continuously increasing and the current U.S. age population is getting younger, cemented fixation may not provide adequate long-term outcomes due to failure of fixation. Thus, there has been a reemergence of the development and use of cementless TKA. Recent short-term trials have demonstrated that modern cementless TKA has comparable survivorship and functional outcomes as cemented prostheses. However, more prospective, randomized trials are needed to clearly delineate any differences between these two fixation options.
Keywords: cementless total knee; noncemented; total knee arthroplasty; implant